A composite material containing carbon nanocones and preparation method thereof
By growing carbon nanocones on the surface of Na3VxM2-x(PO4)3 material, the problem of low conductivity of sodium vanadium phosphate material is solved, significantly improving its conductivity and electrochemical properties, and improving the performance of the material in the rapid charging and discharging process.
Patent Information
- Application Number
- CN202211061527.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-01
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-09-01
AI Technical Summary
The conductivity of sodium vanadium phosphate material is not high, resulting in limited application of its fast charging and discharging.
The conductive and electrochemical properties of carbon nanocones are improved by growing carbon nanocones on the surface of Na3VxM2-x(PO4)3 material. The method includes dispersing vanadium pentoxide, sodium carbonate, ammonium dihydrogen phosphate and metal compounds in water to form a precursor dispersion, which is dried, presintered and calcined, and finally reacted in a gas system to grow carbon nanocones.
The conductivity and electrochemical properties of Na3VxM2-x(PO4)3 material are significantly improved, the electron transfer and sodium ions migration rate during charge and discharge are enhanced, and the magnification and cycling performance of the material are improved.
Smart Images

Figure CN115377384B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode materials, and in particular to a composite material containing carbon nanocones and a preparation method thereof. Background Art
[0002] At present, the new energy industry is developing rapidly, and energy storage applications are mainly focused on lithium-ion batteries. However, due to the limited lithium resources and the increasing demand, researchers have gradually turned their attention to sodium-ion batteries, which are very similar to lithium-ion batteries. The sodium resources in the earth's crust are abundant and cheap, and sodium-ion batteries are considered to be the most promising alternative to lithium-ion batteries. Sodium vanadium phosphate is a positive electrode material for sodium-ion batteries. It has a NASICON-type fast ion conductor structure, a theoretical specific capacity of 117.6mAh / g, a theoretical specific energy of 400Wh / kg, a high output voltage (3.4V), a small volume change during the sodium ion insertion / extraction process, a very stable structure, and good cycle performance. It is currently a hot topic in the research of positive electrode materials for sodium-ion secondary batteries. However, sodium vanadium phosphate materials have poor conductivity and poor rate performance, which restricts the application of sodium vanadium phosphate in fast charging and discharging. At this stage, the improvement direction of sodium vanadium phosphate materials is mainly focused on improving conductivity. Therefore, how to obtain a method to improve the conductivity and electrochemical properties of sodium vanadium phosphate materials is a technical problem that needs to be solved at present. Summary of the invention
[0003] The purpose of the present invention is to provide a composite material containing carbon nanocones and a preparation method thereof, so as to solve the technical problems that conventional sodium vanadium phosphate materials have low electrical conductivity and poor electrochemical performance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a Na3V x M 2-x The preparation method of the (PO4)3 / carbon nanocone composite material comprises the following steps:
[0006] 1) dispersing vanadium pentoxide, sodium carbonate, ammonium dihydrogen phosphate, citric acid monohydrate and a metal compound in water to obtain a precursor dispersion;
[0007] 2) The precursor dispersion is dried, pre-sintered and calcined in sequence to obtain Na3V x M 2-x (PO4)3 precursor;
[0008] 3) Na3V x M 2-x The (PO4)3 precursor is placed in a gas system for reaction to obtain Na3V x M 2-x(PO4)3 / carbon nanocone composite material, wherein M is any one of Mn, Ni, Co, Fe, Zr, Ti, Al, and 0.2≤x≤2.
[0009] Furthermore, the molar ratio of vanadium pentoxide, sodium carbonate, ammonium dihydrogen phosphate and citric acid monohydrate is 1-3:2-4:5-7:3-5; the molar ratio of sodium carbonate and metal compound is 2-4:1-4; the metal compound comprises any one of manganese carbonate, manganese acetate, manganese oxide, nickel carbonate, nickel acetate, nickel oxide, cobalt carbonate, cobalt acetate, cobalt oxide, iron oxide, zirconium carbonate, zirconium acetate, zirconium oxide, titanium oxide and aluminum oxide;
[0010] The molar volume ratio of vanadium pentoxide to water is 1-3 mol:100 mL.
[0011] Furthermore, in the step 2), the drying temperature is 70-90° C., and the drying is performed until the precursor solution is completely evaporated.
[0012] Furthermore, the pre-sintering treatment is preceded by a grinding treatment, the pre-sintering treatment temperature is 300-400° C., the pre-sintering treatment time is 3-5 hours, and the pre-sintering treatment heating rate is 4-6° C. / min.
[0013] Furthermore, the calcination treatment is preceded by a grinding treatment, the calcination treatment temperature is 750-850° C., the calcination treatment time is 9-11 hours, and the calcination treatment heating rate is 4-6° C. / min.
[0014] Furthermore, in the step 3), the reaction temperature is 1000-1050° C., the reaction time is 10-15 min, and the heating rate from room temperature to the reaction temperature is 8-12° C. / min.
[0015] Furthermore, in step 3), after the reaction is completed, the temperature is lowered to room temperature at a rate of 1 to 15°C / min.
[0016] Furthermore, in the step 3), from the start of heating to reaching the reaction temperature, the gas system is argon; during the reaction, the gas system contains argon, hydrogen and ethylene gas; from the end of the reaction to the temperature dropping to 400°C, the gas system contains hydrogen and argon; from 400°C to room temperature, the gas system is argon.
[0017] Furthermore, the flow rate of the argon gas is 40-50 sccm, the flow rate of the hydrogen gas is 40-50 sccm, and the flow rate of the ethylene gas is 1-3 sccm.
[0018] The present invention also provides a Na3V x M 2-x (PO4)3 / carbon nanocone composites.
[0019] Beneficial effects of the present invention:
[0020] The present invention improves Na3V x M 2-x The morphology of (PO4)3 material is achieved by reacting at high temperature using specific gas types and proportions in Na3V x M 2-x Growth of carbon nanocones on (PO4)3 materials, Na3V x M 2-x The carbon nanocones grown on (PO4)3 materials improve the Na3V x M 2-x The conductivity of (PO4)3 material increases the rate of electron transfer and sodium ion migration during charging and discharging, which is conducive to accelerating the reaction and thus improving its electrochemical performance.
[0021] The reaction time of the present invention is short. x M 2-x The carbon nanocones grown on the surface of the (PO4)3 material have uniform and uniform shapes. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the XRD pattern of the composite material obtained in step (2) of Example 1;
[0023] Figure 2 is Na3V in step (1) of Example 1 x M 2-x SEM image of (PO4)3 precursor;
[0024] Figure 3 This is a SEM image of the composite material obtained in step (2) of Example 1;
[0025] Figure 4 is Na3V in Example 1 x M 2-x Rate performance diagram of (PO4)3 precursor and composite material;
[0026] Figure 5 is Na3V in Example 1 x M 2-x Cycling performance diagram of (PO4)3 precursor and composite materials;
[0027] Figure 6 The Na3V obtained in step (2) of Example 2 x M 2-x SEM image of (PO4)3 / carbon nanocone composite material;
[0028] Figure 7 The Na3V obtained in step (2) of Example 3x M 2-x SEM image of (PO4)3 / carbon nanocone composite material. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a composite material containing carbon nanocones, comprising the following steps:
[0030] 1) dispersing vanadium pentoxide, sodium carbonate, ammonium dihydrogen phosphate, citric acid monohydrate and a metal compound in water to obtain a precursor dispersion;
[0031] 2) The precursor dispersion is dried, pre-sintered and calcined in sequence to obtain Na3V x M 2-x (PO4)3 precursor;
[0032] 3) Na3V x M 2-x The (PO4)3 precursor is placed in a gas system for reaction to obtain Na3V x M 2-x (PO4)3 / carbon nanocone composite material, wherein M is any one of Mn, Ni, Co, Fe, Zr, Ti, Al, and 0.2≤x≤2.
[0033] In the present invention, x is preferably 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.5, or 2.0.
[0034] In the present invention, the molar ratio of vanadium pentoxide, sodium carbonate, ammonium dihydrogen phosphate and citric acid monohydrate is 1-3:2-4:5-7:3-5, preferably 1.5-2.5:2.5-3.5:5.5-6.5:3.5-4.5, and more preferably 2:3:6:4.
[0035] In the present invention, the molar ratio of sodium carbonate to the metal compound is 2-4:1-4, preferably 2.5-3.5:1.5-3.5, and more preferably 3:2.
[0036] In the present invention, the metal compound comprises any one of manganese carbonate, manganese acetate, manganese oxide, nickel carbonate, nickel acetate, nickel oxide, cobalt carbonate, cobalt acetate, cobalt oxide, iron oxide, zirconium carbonate, zirconium acetate, zirconium oxide, titanium oxide and aluminum oxide, preferably any one of manganese carbonate, nickel carbonate, zirconium carbonate and aluminum oxide.
[0037] In the present invention, the molar volume ratio of vanadium pentoxide to water is 1 to 3 mol:100 mL, preferably 2 mol:100 mL.
[0038] In the present invention, in the step 2), the drying temperature is 70-90° C., preferably 75-85° C., and more preferably 80° C., and the drying is performed until the precursor solution is completely evaporated.
[0039] In the present invention, the pre-sintering treatment is preceded by a grinding treatment, the pre-sintering temperature is 300-400°C, preferably 320-380°C, and more preferably 350°C; the pre-sintering time is 3-5h, preferably 3.5-4.5h, and more preferably 4h; the heating rate of the pre-sintering treatment is 4-6°C / min, preferably 5°C / min.
[0040] In the present invention, the calcination treatment is preceded by a grinding treatment, the calcination temperature is 750-850°C, preferably 780-820°C, and more preferably 790-800°C; the calcination time is 9-11h, preferably 9.5-10.5h, and more preferably 10h; the heating rate of the calcination treatment is 4-6°C / min, and preferably 5°C / min.
[0041] In the present invention, in the step 3), the reaction temperature is 1000-1050°C, preferably 1020-1040°C, preferably 1030°C; the reaction time is 10-15 min, preferably 11-14 min, more preferably 12-13 min; the heating rate from room temperature to the reaction temperature is 8-12°C / min, preferably 9-11°C / min, more preferably 10°C / min.
[0042] In the present invention, in the step 3), after the reaction is completed, the temperature is lowered to room temperature at a rate of 1 to 15°C / min, preferably 3 to 10°C / min, and more preferably 3 to 7°C / min.
[0043] In the present invention, in the step 3), from the start of heating to reaching the reaction temperature, the gas system is argon; during the reaction, the gas system contains argon, hydrogen and ethylene gas; from the end of the reaction to the temperature dropping to 400°C, the gas system contains hydrogen and argon; from 400°C to room temperature, the gas system is argon.
[0044] In the present invention, the flow rate of the argon gas is 40 to 50 sccm, preferably 42 to 48 sccm, and more preferably 45 sccm.
[0045] In the present invention, the flow rate of the hydrogen gas is 40 to 50 sccm, preferably 42 to 48 sccm, and more preferably 45 sccm.
[0046] In the present invention, the flow rate of the ethylene gas is 1 to 3 sccm, preferably 1 to 2 sccm, and more preferably 2 sccm.
[0047] The present invention also provides a Na3V x M 2-x (PO4)3 / carbon nanocone composites.
[0048] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0049] Example 1
[0050] Preparation of Na3V2(PO4)3 / carbon nanocone composite materials:
[0051] (1) Preparation of sodium vanadium phosphate precursor: Vanadium pentoxide, sodium carbonate, diammonium hydrogen phosphate, and citric acid monohydrate are mixed in a molar ratio of 2:3:6:4 and dissolved in 100 mL of deionized water and stirred to form a precursor solution, wherein the molar concentration of vanadium pentoxide is 0.2 mol / L; the precursor solution is heated and stirred at 80°C until completely evaporated, and the evaporated solid is ground into a uniform powder in a mortar, and then the powder is sent to a tube furnace, raised to 350°C at 5°C / min, and pre-sintered at this temperature for 4 h. After pre-sintering, the powder is taken out and ground again to be uniform; finally, the pre-sintered and uniformly ground powder is sent to a tube furnace, raised to 800°C at 5°C / min, and calcined at this temperature for 10 h to obtain a sodium vanadium phosphate precursor.
[0052] (2) The sodium vanadium phosphate precursor obtained in step (1) is placed in a vapor deposition tube furnace, and the temperature is raised to 1000°C at 10°C / min in a specific gas system by vapor deposition method, and the temperature is reacted at this temperature for 10 minutes, and then the temperature is lowered to room temperature at a rate of 5°C / min to obtain a sodium vanadium phosphate / carbon nanocone composite material with carbon nanocones grown on the surface. The types and flow rates of the gases are ethylene gas 2sccm, hydrogen gas 45sccm, and argon gas 45sccm. The nodes for introducing the gas are: argon gas is kept from the beginning of the temperature increase to the temperature drop to room temperature (i.e., the whole process); hydrogen gas is introduced when the reaction temperature (1000°C) is reached, and the introduction of hydrogen gas is stopped when the reaction is completed and the temperature drops to 400°C; ethylene gas is introduced for 10 minutes when the reaction temperature (1000°C) is reached, and the introduction of ethylene gas is stopped after the 10-minute reaction.
[0053] Example 2
[0054] Preparation of Na3V2(PO4)3 / carbon nanocone composite materials:
[0055] (1) Preparation of sodium vanadium phosphate precursor: Vanadium pentoxide, sodium carbonate, diammonium hydrogen phosphate, and citric acid monohydrate are mixed in a molar ratio of 2:3:6:4 and dissolved in 100 mL of deionized water and stirred to form a precursor solution, wherein the molar concentration of vanadium pentoxide is 0.2 mol / L; the precursor solution is heated and stirred at 85°C until completely evaporated to dryness, and the evaporated solid is ground into a uniform powder in a mortar, and then the powder is sent to a tube furnace, raised to 320°C at 4°C / min, and pre-sintered at this temperature for 4 h. After pre-sintering, the powder is taken out and ground again to be uniform; finally, the pre-sintered and uniformly ground powder is sent to a tube furnace, raised to 820°C at 5°C / min, and calcined at this temperature for 10 h to obtain a sodium vanadium phosphate precursor.
[0056] (2) placing the sodium vanadium phosphate precursor obtained in step (1) into a vapor deposition tube furnace, heating the temperature to 1050° C. at a rate of 10° C. / min in a specific gas system by vapor deposition, reacting at this temperature for 10 minutes, and then cooling the temperature to room temperature at a rate of 8° C. / min to obtain a sodium vanadium phosphate / carbon nanocone composite material with carbon nanocones grown on the surface, wherein the types and flow rates of the gases are 2 sccm of ethylene gas, 45 sccm of hydrogen gas, and 50 sccm of argon gas, respectively. The gas introduction nodes are: argon gas is kept from the start of heating to the temperature drop (i.e., the whole process); hydrogen gas is introduced when the reaction temperature (1050° C.) is reached, and the introduction of hydrogen gas is stopped when the reaction is completed and the temperature drops to 400° C.; ethylene gas is introduced when the reaction temperature (1050° C.) is reached for 10 minutes, and the introduction of ethylene gas is stopped after the 10-minute reaction is completed.
[0057] Example 3
[0058] Preparation of Na3V2(PO4)3 / carbon nanocone composite materials:
[0059] (1) Preparation of sodium vanadium phosphate precursor: Vanadium pentoxide, sodium carbonate, diammonium hydrogen phosphate, and citric acid monohydrate are mixed in a molar ratio of 2:3:6:4 and dissolved in 100 mL of deionized water and stirred to form a precursor solution, wherein the molar concentration of vanadium pentoxide is 0.2 mol / L; the solution is heated and stirred at 80°C until completely evaporated to dryness, and the evaporated solid is ground into a uniform powder in a mortar, and then the powder is sent to a tube furnace, raised to 380°C at a rate of 5°C / min, and pre-sintered at this temperature for 4.5 h. After pre-sintering, the powder is taken out and ground again to be uniform; finally, the pre-sintered and uniformly ground powder is sent to a tube furnace, raised to 800°C at a rate of 5°C / min, and calcined at this temperature for 10 h to obtain a sodium vanadium phosphate precursor.
[0060] (2) The sodium vanadium phosphate precursor obtained in step (1) is placed in a vapor deposition tube furnace, and the temperature is raised to 1050°C at 10°C / min in a specific gas system by vapor deposition method, and the temperature is reacted at this temperature for 15 minutes, and then the temperature is lowered to room temperature at a rate of 10°C / min to obtain a sodium vanadium phosphate / carbon nanocone composite material with carbon nanocones grown on the surface. The types and flow rates of the gases are ethylene gas 2sccm, hydrogen 45sccm, and argon 40sccm. The nodes for introducing the gas are: argon is kept from the beginning of the temperature increase to the temperature drop (i.e., the whole process); hydrogen is introduced when the reaction temperature (1050°C) is reached, and the introduction of hydrogen is stopped when the reaction is completed and the temperature drops to 400°C; ethylene gas is introduced for 15 minutes when the reaction temperature (1050°C) is reached, and the introduction of ethylene gas is stopped after the 15-minute reaction.
[0061] Example 4
[0062] Preparation of Na3VFe(PO4)3 / carbon nanocone composite materials:
[0063] (1) Preparation of sodium vanadium phosphate precursor: Vanadium pentoxide, sodium carbonate, diammonium hydrogen phosphate, citric acid monohydrate and iron oxide were mixed in a molar ratio of 2:3:6:4:1 and dispersed in 100 mL of deionized water and stirred evenly to form a precursor dispersion, wherein the molar concentration of vanadium pentoxide was 0.2 mol / L; the above solution was heated and stirred at 80°C until completely evaporated, and the evaporated solid was ground into a uniform powder in a mortar, and then the powder was sent to a tube furnace, raised to 380°C at 5°C / min, and pre-sintered at this temperature for 4.5 h. After pre-sintering, the powder was taken out and ground again to be uniform; finally, the pre-sintered and uniformly ground powder was sent to a tube furnace, raised to 800°C at 5°C / min, and calcined at this temperature for 10 h to obtain a Na3VFe(PO4)3 precursor.
[0064] (2) The Na3VFe(PO4)3 precursor obtained in step (1) is placed in a vapor deposition tube furnace, and the temperature is raised to 1050°C at a rate of 10°C / min in a specific gas system by vapor deposition method, and the reaction is carried out at this temperature for 15 minutes, and then the temperature is lowered to room temperature at a rate of 10°C / min to obtain a Na3VFe(PO4)3 / carbon nanocone composite material with carbon nanocones grown on the surface. The types and flow rates of the gases are ethylene gas 2sccm, hydrogen gas 45sccm, and argon gas 40sccm. The nodes for introducing the gas are: argon gas is kept from the beginning of the temperature increase to the temperature drop (i.e., the whole process); hydrogen gas is introduced when the reaction temperature (1050°C) is reached, and the introduction of hydrogen gas is stopped when the reaction is completed and the temperature drops to 400°C; ethylene gas is introduced when the reaction temperature (1050°C) is reached for 15 minutes, and the introduction of ethylene gas is stopped after the 15-minute reaction is completed.
[0065] Example 5
[0066] Preparation of Na3VMn(PO4)3 / carbon nanocone composite materials:
[0067] (1) Preparation of sodium vanadium phosphate precursor: Vanadium pentoxide, sodium carbonate, diammonium hydrogen phosphate, citric acid monohydrate and manganese acetate were mixed in a molar ratio of 2:3:6:4:2 and dispersed in 100 mL of deionized water and stirred evenly to form a precursor dispersion, wherein the molar concentration of vanadium pentoxide was 0.2 mol / L; the above solution was heated and stirred at 80°C until completely evaporated to dryness, and the evaporated solid was ground into a uniform powder in a mortar, and then the powder was sent to a tube furnace, raised to 380°C at 5°C / min, and pre-sintered at this temperature for 4.5 h. After pre-sintering, the powder was taken out and ground again to be uniform; finally, the pre-sintered and uniformly ground powder was sent to a tube furnace, raised to 800°C at 5°C / min, and calcined at this temperature for 10 h to obtain a Na3VMn(PO4)3 precursor.
[0068] (2) The Na3VMn(PO4)3 precursor obtained in step (1) is placed in a vapor deposition tube furnace, and the temperature is raised to 1050°C at a rate of 10°C / min in a specific gas system by vapor deposition method, and the reaction is carried out at this temperature for 15 minutes, and then the temperature is lowered to room temperature at a rate of 10°C / min to obtain a Na3VMn(PO4)3 / carbon nanocone composite material with carbon nanocones grown on the surface. The types and flow rates of the gases are ethylene gas 2sccm, hydrogen 45sccm, and argon 40sccm. The nodes for introducing the gas are: argon is kept from the beginning of the temperature increase to the temperature drop (i.e., the whole process); hydrogen is introduced when the reaction temperature (1050°C) is reached, and the introduction of hydrogen is stopped when the reaction is completed and the temperature drops to 400°C; ethylene gas is introduced for 15 minutes when the reaction temperature (1050°C) is reached, and the introduction of ethylene gas is stopped after the 15-minute reaction.
[0069] The product obtained in Example 1 was subjected to XRD and SEM tests. The test results are as follows Figures 1 to 3 shown.
[0070] like Figure 1 As shown, the test results of the sodium vanadium phosphate / carbon nanocone composite material obtained in step (2) of Example 1 show pure diffraction peaks, which correspond one-to-one with the sodium vanadium phosphate standard card, and no diffraction peaks related to carbon appear, indicating that the carbon nanocones grown on the surface of the sodium vanadium phosphate are not stacked in large quantities, but are evenly grown on the sodium vanadium phosphate crystals.
[0071] like Figure 2 As shown, the sodium vanadium phosphate precursor without vapor deposition treatment presents a blocky morphology; Figure 3This is the SEM image of the sodium vanadium phosphate / carbon nanocone composite material obtained in step (2) of Example 1. It can be seen that a pointed cone-shaped carbide grows on the surface of the sodium vanadium phosphate. The widest width of the bottom of the pointed cone-shaped carbide is about 400nm, and the shape is very uniform and uniform. Figure 6 and Figure 7 are SEM images of the sodium vanadium phosphate / carbon nanocone composite materials obtained in Example 2 and Example 3, and Figure 3 Similarly, it can be seen that the surface of sodium vanadium phosphate also grows cone-shaped carbides, the widest width of the bottom of the cone-shaped carbides is about 300nm and 350nm, and the shape is very uniform and unified.
[0072] The sodium vanadium phosphate precursor in step (1) of Example 1 and the sodium vanadium phosphate / carbon nanocone composite material obtained in step (2) were assembled into sodium ion batteries, and the cycle and rate performance tests were performed. The test results are as follows: Figures 4-5 shown.
[0073] pass Figure 4 Test results show that the rate performance of the sodium vanadium phosphate / carbon nanocone composite material synthesized by the present invention is better than that of the untreated sodium vanadium phosphate precursor. The discharge specific capacities at 0.1C, 0.2C, 0.5C, 2C, 5C and 10C are 115.11, 114.43, 113.47, 112.21, 110.37 and 107.84 mAh / g, respectively. When the current rate returns to 0.1C, the discharge specific capacity can still reach 113.53 mAh / g. The untreated sodium vanadium phosphate has discharge specific capacities of 114.95, 86.6, 59.66, 35.39, 21 and 1.77 mAh / g at 0.1C, 0.2C, 0.5C, 2C, 5C and 10C, respectively. When the current rate returns to 0.1C, the discharge specific capacity is only 85 mAh / g.
[0074] pass Figure 5 It can be seen that the sodium vanadium phosphate / carbon nanocone composite material obtained in step (2) exhibits a higher cycle retention rate than the untreated sodium vanadium phosphate precursor.
[0075] The Na3VFe(PO4)3 / carbon nanocone composite materials and Na3VMn(PO4)3 / carbon nanocone composite materials obtained in Examples 4 to 5 were tested to show the same conductivity and discharge cycle retention rate as those in Example 1. It can be seen that the preparation method of the present invention can be applied to sodium vanadium phosphate materials doped with various elements, and can also obtain good electrochemical properties.
[0076] From the above examples, it can be seen that the present invention provides a composite material containing carbon nanocones and a preparation method thereof. The preparation method of the present invention realizes the x M 2-x(PO4)3 carbon nanocones are grown on the surface of the substrate. This preparation method is simple to operate and improves the Na3V x M 2-x The conductivity of (PO4)3 material increases the Na3V x M 2-x The reaction rate of (PO4)3 material with sodium ions during the charge and discharge process.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A Na3V x M 2-x The method for preparing a (PO4)3 / carbon nanocone composite material is characterized in that: The following steps are involved: 1) dispersing vanadium pentoxide, sodium carbonate, ammonium dihydrogen phosphate, citric acid monohydrate and a metal compound in water to obtain a precursor dispersion; 2) The precursor dispersion is dried, pre-sintered and calcined in sequence to obtain Na3V x M 2-x (PO4)3 precursor; 3) Na3V x M 2-x The (PO4)3 precursor is placed in a gas system for reaction to obtain Na3V x M 2-x (PO4)3 / carbon nanocone composite material, wherein M is any one of Mn, Ni, Co, Fe, Zr, Ti, Al, 0.2≤x≤2; The molar ratio of vanadium pentoxide, sodium carbonate, ammonium dihydrogen phosphate and citric acid monohydrate is 1-3:2-4:5-7:3-5; the molar ratio of sodium carbonate and metal compound is 2-4:1-4; the metal compound comprises any one of manganese carbonate, manganese acetate, manganese oxide, nickel carbonate, nickel acetate, nickel oxide, cobalt carbonate, cobalt acetate, cobalt oxide, iron oxide, zirconium carbonate, zirconium acetate, zirconium oxide, titanium oxide and aluminum oxide; The molar volume ratio of vanadium pentoxide to water is 1 to 3 mol:100 mL; In the step 3), the reaction temperature is 1000-1050°C, the reaction time is 10-15 min, and the heating rate from room temperature to the reaction temperature is 8-12°C / min; In the step 3), the temperature is cooled to room temperature at a rate of 1 to 15°C / min after the reaction is completed; In the step 3), from the start of heating to the reaching of the reaction temperature, the gas system is argon; during the reaction, the gas system contains argon, hydrogen and ethylene gas; from the end of the reaction to the temperature dropping to 400°C, the gas system contains hydrogen and argon; from 400°C to room temperature, the gas system is argon.
2. Na3V according to claim 1 x M 2-x The method for preparing a (PO4)3 / carbon nanocone composite material is characterized in that: In the step 2), the drying temperature is 70-90° C., and the drying is performed until the precursor solution is completely evaporated.
3. Na3V according to claim 1 or 2 x M 2-x The method for preparing a (PO4)3 / carbon nanocone composite material is characterized in that: The pre-sintering treatment is preceded by a grinding treatment, the pre-sintering temperature is 300-400° C., the pre-sintering time is 3-5 hours, and the pre-sintering heating rate is 4-6° C. / min.
4. Na3V according to claim 3 x M 2-x The method for preparing a (PO4)3 / carbon nanocone composite material is characterized in that: The calcination treatment is preceded by a grinding treatment, the calcination temperature is 750-850° C., the calcination time is 9-11 hours, and the heating rate of the calcination is 4-6° C. / min.
5. Na3V according to claim 4 x M 2-x The method for preparing a (PO4)3 / carbon nanocone composite material is characterized in that: The flow rate of the argon gas is 40-50 sccm, the flow rate of the hydrogen gas is 40-50 sccm, and the flow rate of the ethylene gas is 1-3 sccm.
6. Na3V obtained by the preparation method according to any one of claims 1 to 5 x M 2-x (PO4)3 / carbon nanocone composite material, characterized in that The Na3V x M 2-x Carbon nanocone structures grow on the surface of the (PO4)3 / carbon nanocone composite material.
Citation Information
Patent Citations
Graphene / carbon coated lithium manganese phosphate-lithium vanadium phosphate positive electrode material and preparation method thereof
CN107910538A
Sodium-rich sodium-ion battery cathode material and preparation method thereof
CN109437142A